The Associations Between Physical Activity and Mental Health Problems in Middle-aged Indonesians - Sri Handayani; Siti Isfandari; Diyan Ermawan Effendi; Rozana Ika Agustiya; Irfan Ardani; Arief Priyo Nugroho; Yunita Fitrianti (Journal of Preventive Medicine and Public Health, 2024)
Objectives: Mental health issues have become a growing concern worldwide. Research has shown that regular physical activity (PA) can positively affect mental health. This study investigated the associations between PA and mental health problems (MHPs) in middle-aged Indonesians. Methods: The study utilized data from the 2018 Indonesian Basic Health Research Survey and used a cross-sectional approach. The participants included individuals aged 40-60 years who completed the 20-question Self-Reporting Questionnaire. A logistic regression was performed to analyze a sample of 263 930 data points. Results: Nearly 10.4% of the participants suffered from mental health issues. Notably, among those who did not engage in moderate and vigorous PA, a sign of MHPs was found in 12.5% of participants. Those who met World Health Organization standards for PA were less likely to experience MHPs (10.1%). This study found a significant association between PA and mental health. After adjusting for smoking, alcohol consumption, non-communicable diseases, and socio-demographic variables like age, sex, education, occupation, marital status, and residence, the connection between PA and mental health became even stronger (adjusted odds ratio, 0.81; 95% confidence interval, 0.78 to 0.85; p<0.001). Conclusions: Regular PA has been shown to affect mental health positively. Therefore, it is important to improve health education and efforts to raise awareness among middle-aged Indonesians about the importance of PA in maintaining good mental health.